TABOO LANGUAGE EXPRESSED IN AMERICAN FILM "CRANK 2" - RAHMA, ROSIKAH (Jurnal Ilmiah Mahasiswa FIB, 2015)
Keywords: Taboo, types of taboo words, types of anger express, Crank 2. In communication, people use many language. Sometimes people use formal and informal language in communication. Many people communicate with inapproriate language as speaking with friends or family by using impolite language for example taboo language.As we know, taboo language is an unfavourable language in society. But, taboo language becomes common phenomenon today. People free to speak what they want, there are many people used taboo language to express feeling and emotion. American modern hear taboo language in street, at home, at school, in the radio, in television, etc. Today, Film is growing rapidly, the reason is many genre of film appears to amuse the audience. One of the genre film is action, and one of the action film is “Crank 2”. Many characters use taboo language. This film showed that social life influence the use of language.This study uses qualitative approach which refers to document analysis about the phenomena of taboo language in conversations done by the main characters  in “Crank 2” film. The data of this study are the utterances which contain taboo words produced by the main character, furthermore the writer collects the data according to Timothy Jay’s theory (1996).The writer found out taboo words uterred by Chev Chelios. The main character used 4 types of taboo words as follows : blasphemy (Jesus Christ), obscenity (fucking, shit, dick, fuck, cunt, ass, fucker, motherfucker), sexual harassement (bastard, bitch, whore), and insult(chinese man, slant-eye). Then, the writer found that Chev Chelios uses 6 types of anger expressed as follows : Social-Sexual Deviation (whore, bitch), racial-ethnic reference (Chinese an, slanteye), curse and blaspemy (Jesus Christ), obscenity (fucking, dick, fuck, fucker, motherfucker, cunt and ass), subnormal though (bastard), and scatology (shit).The writer would like to give some suggestion for the next researcher who wants to conduct a similar research to find out the use of taboo language using other theories. Furthermore, the next researcher can be used other objects such as novel, comic, or daily activity.